Transcriptional Regulator YqeI, Locating at ETT2 Locus, Affects the Pathogenicity of Avian Pathogenic Escherichia coli - Mei Xue; Yating Xiao; Dandan Fu; Muhammad Akmal Raheem; Ying Shao; Xiangjun Song; Jian Tu; Ting Xue; Kezong Qi (Animals, 2020)
Avian pathogenic Escherichia coli (APEC) is the leading cause of systemic infections in poultry worldwide and has a hidden threat to public health. Escherichia coli type three secretion system 2 (ETT2), similar to the Salmonella pathogenicity island SPI1, is widely distributed in APEC and associated with virulence. The function of YqeI, which is one of the hypothetical transcriptional regulators locating at the ETT2 locus of APEC, is unknown. In this study, we successfully obtained the mutant strain AE81ΔyqeI of the wild type strain AE81 and performed the transcriptional profiling assays. Additionally, the transcriptional sequencing results revealed that YqeI influenced localization, locomotion and biological adhesion and so on. The transmission electron microscope observation showed that the wild type strain AE81 possessed long curved flagella, whereas the mutant strain AE81ΔyqeI hardly had any. The strain AE81ΔyqeI exhibited lower motility than AE81 after culturing the dilute bacterial suspension on a semisolid medium. It was also found that the survival ability of AE81ΔyqeI weakened significantly when AE81ΔyqeI was cultured with 0%, 10%, 20%, 30%, 40% and 50% SPF serum in PBS, and AE81ΔyqeI had decreased adherence to DF-1 cells compared with AE81 in the bacterial adhesion assay. The bacterial colonization assay indicated that the virulence of AE81ΔyqeI was reduced in the heart, liver, spleen, and lung. These results confirmed that the transcription regulator YqeI is involved in APEC’s pathogenicity, and this study provides clues for future research.